Muhammadiyah Studies: The Transformation of Research on Islamic Movement in Indonesia - Mutohharun Jinan (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This research aims to describe the studies of the Muhammadiyah movement. Scholars have condukted research, observations, and discussions of the Movement. This research is not limited the Muhammadiyah as an Islamic movement, but also its role as economic,educational, and socio-political movement. Research and discussion on the various dimensions of Muhammadiyah are called